Legal Applicability of the Employment Social Security Program in Aceh: Perspective of Aceh Qanun Number 11 of 2018 - Renggha Prima; Dewi Sulistianingsih (Universitas Negeri Semarang, 2025)
The implementation of Islamic law in Aceh is a form of state recognition of the special status of the region based on the long history of the struggle of the Acehnese people who demonstrated their resilience and fighting spirit. Law Number 44 of 1999 concerning the Implementation of Special Status for the Special Region of Aceh emphasizes the importance of maintaining customs and the role of religious scholars in community life. Aceh as a special region has the authority to regulate government affairs and regional interests in accordance with Law Number 11 of 2006. These special statuses include the implementation of religious life based on Islamic teachings, the position of customary law, education based on Islamic principles, and the role of religious scholars in formulating policies or Qanun. One of the most significant regulations is Aceh Qanun Number 11 of 2018 concerning Islamic Financial Institutions which aims to develop the economy of the Acehnese people in accordance with sharia principles. This study aims to analyze the policies or Qanun in financial institutions, including the Employment Social Security Agency, which is required to apply sharia principles in its operational activities in Aceh. This study uses a qualitative approach with data collection through literature studies. The results of the study indicate that the Employment Social Security Agency Program implemented in Aceh Province is in line with sharia principles, although some improvements and harmonization of regulations governing employment social security are still needed.